Electronic Evidence - Mason, Stephen; Seng, Daniel (OBserving Law, 2017)
In this updated edition of the well-established practitioner text, Stephen Mason and Daniel Seng have brought together a team of experts in the field to provide an exhaustive treatment of electronic evidence. This fourth edition continues to follow the tradition in English evidence text books by basing the text on the law of England and Wales, with appropriate citations of relevant case law and legislation from other jurisdictions. Stephen Mason (of the Middle Temple, Barrister) is a leading authority on electronic evidence and electronic signatures, having advised global corporations and governments on these topics. He is also the author of Electronic Signatures in Law and editor of International Electronic Evidence, founding the innovative international open access journal Digital Evidence and Electronic Signatures Law Review in 2004. Stephen is an IALS Associate Research Fellow and Visiting Lecturer at the School of Law, University of Tartu, Estonia. Daniel Seng (Associate Professor, National University of Singapore) teaches and researches on information technology law, infocommunications law, evidence and procedure, artificial intelligence, machine learning and legal reasoning. His research interests also include empirical legal studies and quantitative research and data analytics on big data sets. Between 2001 and 2003, he was concurrently the Director of Research, Technology Law Development Group at the Singapore Academy of Law. Daniel is also a special consultant to the World Intellectual Property Organization, where he has researched, delivered papers and published monographs on copyright exceptions for academic institutions, music copyright in the Asia Pacific and the liability of Internet intermediaries. He is also a non-residential fellow with the Centre for Legal Informatics (CodeX), Stanford University. This book is also available online at http://ials.sas.ac.uk/digital/humanities-digital-library/observing-law-ials-open-book-service-law.